Lyme Disease Testing in a High-Incidence State: Clinician Knowledge and Patterns. Issue 3 (7th February 2018) - Conant, Joanna L; Powers, Julia; Sharp, Gregory; Mead, Paul S; Nelson, Christina A
Abstract: Objectives: Lyme disease (LD) incidence is increasing, but data suggest some clinicians are not fully aware of recommended procedures for ordering and interpreting diagnostic tests. The study objective was to assess clinicians' knowledge and practices regarding LD testing in a high-incidence region. Methods: We distributed surveys to 1, 142 clinicians in the University of Vermont Medical Center region, of which 144 were completed (12.6% response rate). We also examined LD laboratory test results and logs of calls to laboratory customer service over a period of 2.5 years and 6 months, respectively. Results: Most clinicians demonstrated basic knowledge of diagnostic protocols, but many misinterpreted Western blot results. For example, 42.4% incorrectly interpreted a positive immunoglobulin M result as an overall positive test in a patient with longstanding symptoms. Many also reported receiving patient requests for unvalidated tests. Conclusions: Additional education and modifications to LD test ordering and reporting systems would likely reduce errors and improve patient care.